Pervasive admixture and the spread of a large‐lipped form in a cichlid fish radiation. Issue 21 (16th September 2021) - Sowersby, Will; Cerca, José; Wong, Bob B. M.; Lehtonen, Topi K.; Chapple, David G.; Leal‐Cardín, Mariana; Barluenga, Marta; Ravinet, Mark
Abstract: Adaptive radiations have proven important for understanding the mechanisms and processes underlying biological diversity. The convergence of form and function, as well as admixture and adaptive introgression, are common in adaptive radiations. However, distinguishing between these two scenarios remains a challenge for evolutionary research. The Midas cichlid species complex ( Amphilophus spp.) is a prime example of adaptive radiation, with phenotypic diversification occurring at various stages of genetic differentiation. One species, A . labiatus, has large fleshy lips, is associated with rocky lake substrates, and occurs patchily within Lakes Nicaragua and Managua. By contrast, the similar, but thin‐lipped, congener, A . citrinellus, is more common and widespread. We investigated the evolutionary history of the large‐lipped form, specifically regarding whether the trait has evolved independently in both lakes from ancestral thin‐lipped populations, or via dispersal and/or admixture events. We collected samples from distinct locations in both lakes, and assessed differences in morphology and ecology. Using RAD‐seq, we genotyped thousands of SNPs to measure population structure and divergence, demographic history, and admixture. We found significant between‐species differences in ecology and morphology, local intraspecific differences in body shape and trophic traits, but only limited intraspecific variation in lip shape. Despite clear ecological differences, our genomic approach uncovered pervasive admixture between the species and low genomic differentiation, with species within lakes being genetically more similar than species between lakes. Taken together, our results suggest a single origin of large‐lips, followed by pervasive admixture and adaptive introgression, with morphology being driven by local ecological opportunities, despite ongoing gene‐flow. Resumen: Las radiaciones adaptativas han demostrado ser clave para entender los mecanismos y procesos responsables de la diversidad biológica. La convergencia en forma y función, así como la mezcla genética y la introgresión adaptativa, son algo común en las radiaciones adaptativas. Sin embargo, distinguir entre estos dos escenarios sigue siendo un desafío para la biología evolutiva. El complejo de especies del cíclido de Midas ( Amphilophus spp.) es un ejemplo paradigmático de radiación adaptativa, con diversidad fenotípica en varias etapas de diferenciación genética. Una de las especies, A. labiatus, que tiene labios grandes y carnosos, se asocia a zonas rocosas de los lagos, y tiene una distribución irregular en los lagos Nicaragua y Managua. En cambio, A. citrinellus, es una especie similar pero con labios finos, más común y con una distribución más amplia. Investigamos la historia evolutiva de la especie de labios grandes y, en concreto, si este rasgo ha evolucionado de forma independiente en los dos grandes lagos nicaragüenses a partir de poblaciones ancestrales de labios finos, o si por el contrario se ha dispersado mediante migración y/o mezcla genética. Colectamos muestras de distintas localidades en ambos lagos y evaluamos las diferencias en morfología y ecología. Genotipamos miles de SNPs utilizando RAD‐seq para medir la estructura genética, la divergencia, la historia demográfica y la mezcla genética de las poblaciones. Encontramos diferencias significativas entre especies en ecología y morfología, diferencias intraespecíficas locales en la forma del cuerpo y rasgos tróficos, pero sólo una limitada variación intraespecífica en la forma de los labios. A pesar de las claras diferencias ecológicas, el análisis genómico desveló una intensa mezcla genética entre especies, y una limitada diferenciación genómica, encontrando mayor semejanza genética entre especies dentro de un mismo lago, que entre especies de distintos lagos. Nuestros resultados sugieren un origen único de la especie de labios gruesos seguido de mezcla genética e introgresión adaptativa, e indican que la morfología habría sido modelada por las oportunidades ecológicas locales, a pesar del flujo génico.